STUDY OF RECOMMENDATIONS FOR SUSTAINABLE FOOD AGRICULTURAL LAND PROTECTION IN DETERMINING REGIONAL SPATIAL PLANNING SOUTHEAST ACEH DISTRICT CASE STUDY - Mas Pratono; Feby Milanie (Bulletin of Engineering Science, Technology and Industry, 2024)
Protecting sustainable food agricultural land is an important component as a forerunner in recommendations for the demolition of space as a food crop area plan, especially in Southeast Aceh Regency which has great potential in the agricultural sector. This research aims to analyze the challenges and opportunities in integrating urban development and agricultural land conservation, as well as providing strategic recommendations in determining the Regional Spatial Planning (RTRW) in Southeast Aceh Regency. The research method used is a qualitative approach with a case study in Southeast Aceh Regency. This research involves agricultural extension workers as executors in collecting data and filling in agricultural attributes based on actual conditions in the field which will later be processed into spatial data to become spatial data on potential land in Southeast Aceh Regency. The data analysis method was carried out using content analysis techniques to identify relevant main themes. This research involves the working group (Pokja) on sustainable food agricultural land (LP2B) as stakeholders who provide input regarding policies, directions and technical provisions in recommendations for the protection of sustainable food agricultural land. Current zoning policies and Regional Spatial Planning (RTRW) are not yet fully effective in protecting agricultural land. The government needs to strengthen regulations and introduce economic incentives to encourage farmers to defend their land. The establishment of conservation areas is also important to maintain biodiversity and important ecosystems. A sustainable development approach through Smart Growth strategies and green infrastructure can reduce urban land expansion and improve environmental quality. Community participation in the spatial planning process is also very important. Public involvement through consultation forums and environmental education programs can increase awareness of the importance of protecting agricultural land. The use of technology such as geographic information systems and remote sensing is very helpful in monitoring land use changes and planning sustainable urban development. This technology enables accurate spatial data management to support decision making. The strategic recommendations provided include strengthening agricultural land protection regulations, providing economic incentives to farmers, adopting sustainable development principles in spatial planning, and increasing environmental education programs. In addition, the use of geographic information system technology must be optimized for effective land mapping and monitoring. In conclusion, protecting food agricultural land in determining RTRW in Southeast Aceh Regency requires a holistic approach that includes appropriate policies, good planning, community participation and use of technology.With this approach, urban development can take place in a sustainable manner without sacrificing land which is important for food security and environmental sustainability.